Geochronological evidence for the Alpine tectono-thermal evolution of the Veporic Unit (Western Carpathians, Slovakia) - Vojtko, R.; Králiková, S.; Jerábek, P.; Schuster, R.; Danišík, Martin; Fügenschuh, B.; Minár, J.; Madarás, J. (Elsevier BV, 2016)
Tectono-thermal evolution of the Veporic Unit was revealed by multiple geochronological methods, including 87Rb/86Sr on muscovite and biotite, zircon and apatite fission-track, and apatite (U-Th)/He analysis. Based on the new data, the following Alpine tectono-thermal stages can be distinguished: The Eo-Alpine Cretaceous nappe stacking (~135-95 Ma) resulted in burial of the Veporic Unit beneath the northward overthrusting Gemeric Unit and overlying Jurassic Meliata accretionary wedge. During this process the Veporic Unit reached metamorphic peak of greenschist- to amphibolite facies accompanied by orogen-parallel flow in its lower and middle crust. The subsequent evolution of this crust is associated with two distinct exhumation mechanisms related to collision with the northerly Tatric-Fatric basement. The first mechanism (~90-80 Ma) is associated with internal subhorizontal shortening of the Veporic Unit reflected by large-scale upright folding and heterogeneous exhumation of the Veporic lower crust in the cores of crustal-scale antiforms. This led to juxtaposition of the higher and lower grade parts of basement, all cooled down to ~350 °C by ~80 Ma. The second mechanism is associated with the overthrusting of the Veporic Unit over the attenuated Fatric crust. This led to a passive en-block exhumation of the Veporic crust from ~350 °C to 60 °C between ~80 and 55 Ma followed by erosion (~55-35 Ma). The erosion processes resulted in formation of planation surface before the Late Eocene transgression. After erosion and planation, a new sedimentary cycle of the Central Carpathian Palaeogene Basin was deposited with the sedimentary strata thickness of ~1.5-2.0 km (~21-17 Ma). The early to middle Miocene is characterised by destruction tectonic disintegration and erosion of this basin (~20-13 Ma) and formation of the Neogene Vepor Stratovolcano (~13 Ma). The final shaping of the area has been linked to erosional processes of the volcanic structure since the Late Sarmatian with accelerated processes during the Plio-Quaternary.